Chest Pain with Normal Coronary Arteries A Multidisciplinary Approach - Kaski, Juan Carlos; Eslick, Guy D.; Bairey Merz, C. Noel.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The condition known as (3z(Bchest pain with normal coronary arteries(3y (Bor (3z(Bcardiac syndrome X(3y (Bhas puzzled physicians since the advent of coronary arteriography. Although epicardial coronary artery spasm, as seen in Prinzmetal$1 (Bs variant angina, explains a proportion of cases of typical chest pain despite normal coronary arteriograms, many patients who seek medical attention for exertional and rest angina in the absence of obstructive coronary artery disease are not variant angina cases. This syndrome therefore constitutes both a diagnostic and therapeutic challenge. Chest Pain with Normal Coronary Arteries has been written by many of the most active international research groups and comprehensively tackles the clinical presentation and the pathogenesis of the condition, as well as its management. Abnormalities of the coronary microcirculation have remained elusive to conventional imaging and researchers appear only recently to be making progress in obtaining much needed information in this field. The functional aspects of the coronary microcirculation, its clinical presentation and prognosis, as well as the diagnostic tests used for the assessment of microvascular dysfunction are important topics highlighted in this book, which also includes useful clinical diagnostic algorithms, thus bringing this subject closer to the practicing cardiologist. This book thus represents a practical tool for the clinician and a bank of information and new ideas for research scientists and clinical researchers interested in understanding the causes and mechanisms of the condition.s
Keywords: Medicine; Medicine & Public Health; Medicine/Public Health, general